ANALISIS MULTIPLE INTELLIGENCE PESERTA DIDIK SEKOLAH DASAR DALAM PEMBELAJARAN KURIKULUM MERDEKA - Fiandita Aghnia (Tunas Nusantara, 2023)
Intelligence is one part of the learner's learning profile that is important to note. An individual's intelligence can be divided into numerous categories, including logical-mathematical, linguistic, musical, naturalist, visual-spatial, intrapersonal, kinesthetic, and visual-spatial. It is crucial for teachers to assess and develop students' intellect effectively given the variability of their intelligence. The correct learning technique can be used in the classroom to help students reach their full potential based on their intelligence. The idea of the learning  curriculum Merdeka is learning based on the diversity of student profiles. The purpose of this study is to identify the many intelligences of SD Negeri Ngaliyan 01 class IVA students. Descriptive research methodologies are being used in this study with observational data collection techniques and questionnaires. The data analysis technique used is descriptive qualitative .  The results showed a percentage of logical-mathematical intelligence of 8.33%, linguistic intelligence of 4.17%, kinesthetic intelligence of 20.8%, spatial visual intelligence of 12.5%, musical intelligence of 16.7%, naturalistic intelligence of 8.33%, interpersonal intelligence of 8.33%, and intrapersonal intelligence of 20.8%. As a result, the multiple intelligences of each student have different levels